Automated Chromosome Classification for Karyotype Construction Using Deep Learning - Speggiorin, Laura G.; Kowalski, Thayne W.; Jung, Claudio R.; Recamonde-Mendoza, Mariana (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS), 2025)
This project aims to automate human karyotype generation to optimize cytogenetic analysis, seeking to improve accuracy and reduce manual workload. Using a public dataset, the YOLOv10 model was employed for chromosome detection, demonstrating a mean average performance of 99.4%. For segmentation, the SAM model was used as a proof of concept, proving very successful in most cases for generating masks, although it faces challenges with overlapping chromosomes. In conclusion, the detection achieved excellent performance, and segmentation is promising with room for improvement.